Atomic Charge Reveals Global Electron Redistribution in Substituted Benzene: A Semiempirical Quantum Study - Annisha Noor Dienna; Maula Nabila Alika Fitri; Novalia Nurbaiti; Prisca Caesa Moneteringtyas; Keysia Claudia Sagala (TECHNO: JURNAL PENELITIAN, 2026)
This study investigates the electronic influence of electron-donating substituents on the C₀ of substituted benzene systems using a computational chemistry approach. Aromatic systems exhibit complex electron density redistribution governed by π-electron delocalization, where substituent effects propagate across the entire ring rather than remaining localized. To systematically evaluate this behavior, eleven benzene derivatives representing alkyl, amino, and oxygen-containing substituents were modeled and analyzed using the semiempirical AM1 method implemented in ORCA. Atomic charge variations at the C₀ position were calculated relative to benzene and examined using both Mulliken and Löwdin population analyses to ensure methodological consistency. The results reveal that electron-donating groups do not necessarily increase electron density locally at the C₀; instead, the donated electron density is redistributed throughout the aromatic π-system. Alkyl substituents show minimal charge variation, indicating weak inductive effects, while amino groups exhibit moderate influence through resonance interactions without significant localization at C₀. Oxygen-containing substituents, particularly phenol and alkoxy derivatives, demonstrate stronger electronic perturbations due to effective lone-pair resonance donation. Notably, ethoxybenzene displays anomalous behavior, suggesting a combined influence of resonance and additional inductive contributions from its alkyl chain. Despite differences in absolute values, both population analysis methods produce consistent trends, supporting the robustness of the findings. Overall, this study highlights that ΔC₀ serves as an indicator of global electron redistribution rather than localized charge accumulation, providing a more physically meaningful interpretation of substituent effects in aromatic systems